Odpowiedzi

Najlepsza Odpowiedź!
2010-02-23T14:01:32+01:00
A)
an+1=4-(n+1)do 2=4-(n do kwadratu+2n*1+1)=4-n do 2-1=3-n do 2-2n
an+1-an=3-n do 2-2n-4-n do2=-2 do2-2n-1 malejacy

b)
an+1=3(n+1)/4+(n+1)=3n+3/4+n+1=3+3/5+n
an+1-an=3n+3-n+4/n+5*3n=(3n+3)-(n-4)/(n+5)*3n=2n-1/(n+5)*3n

c)
tu nie napi8sales n tylko an=2+1/2 wiec moim zdaniem tego nie rozwiazesz

d)
an+1=(n+1)do2-5(n+1)+4=n do2+2n+1-5n-5+4=n do2+2n+1-5n-5+4=n do2-3n
an+1-an=n do2-3n-n do2-5n+4=-8n+4

e)
an+1=2n-1/-2n+3
an+1-an=4n-6/(-2n+3)(2n-3)